2019
DOI: 10.1111/lang.12370
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Consistency in First and Second Language Processing: A Masked Morphological Priming Study on Prefixation and Suffixation

Abstract: Word forms such as walked or walker are decomposed into their morphological constituents (walk + –ed/–er) during language comprehension. Yet, the efficiency of morphological decomposition seems to vary for different languages and morphological types, as well as for first and second language speakers. The current study reports results from a visual masked priming experiment focusing on different types of derived word forms (specifically prefixed vs. suffixed) in first and second language speakers of German. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 69 publications
2
12
0
1
Order By: Relevance
“…By contrast, derivational and compound priming seem to be more robust and stable across different groups of speakers (L1 and L2) and types of items; see e.g. González Alonso, Baquero Castellanos, and Müller (2016) (2017), Silva and Clahsen (2008) and Ciaccio and Clahsen (2019) for derivation. Taken together, these findings suggest that inflectional priming is less robust across different speaker groups and item types than priming with derived and compound words.…”
Section: Previous Research On Inflectional Priming and Prefixationmentioning
confidence: 99%
“…By contrast, derivational and compound priming seem to be more robust and stable across different groups of speakers (L1 and L2) and types of items; see e.g. González Alonso, Baquero Castellanos, and Müller (2016) (2017), Silva and Clahsen (2008) and Ciaccio and Clahsen (2019) for derivation. Taken together, these findings suggest that inflectional priming is less robust across different speaker groups and item types than priming with derived and compound words.…”
Section: Previous Research On Inflectional Priming and Prefixationmentioning
confidence: 99%
“…To date, very little research has aimed to test whether sublexical processing efficiency, particularly morphological processing efficiency, would be a dimension of lexical competence that may uniquely predict L2 reading comprehension along with other dimensions (lexical vs. sublexical/morphological knowledge, on the one hand, and lexical processing efficiency, on the other hand). Overall, despite increasing interest in morphological knowledge and L2 reading comprehension (e.g., Ke et al., 2021; Kieffer & Lesaux, 2008; Zhang & Koda, 2012) and L2 morphological processing and lexical representation (Clahsen, Felser, Neubauer, Sato, & Silva, 2010; see also Ciaccio & Clahsen, 2020), little effort has been expended to combine the two lines of research and to examine how morphological processing efficiency may have a unique role to play during text reading. Logic suggests that if morphological knowledge is important for lexical inferencing and/or word decoding fluency during text comprehension, as some L2 studies have suggested (e.g., Zhang & Koda, 2012), the use of or access to this knowledge must occur in a rapid manner for comprehension to be smooth and efficient.…”
Section: Background Literaturementioning
confidence: 99%
“…Zudem legen diese Studien den Fokus tendenziell eher auf die Rechtschreibung (Kargl et al, 2014;Kargl et al, 2018). Seit 2015 wurden wichtige Priming-Studien zum Lesen durchgeführt (Bosch & Clahsen, 2016;Ciaccio & Clahsen, 2019;Hasenäcker et al, 2015;. Erfreulicherweise weisen neuere, gängige Lehrbücher zum Schriftspracherwerb und zu Lese-Rechtschreibstörungen auf die Bedeutung der morphologischen Bewusstheit im frühen Schriftspracherwerb der Schriftsprache Deutsch hin (Klicpera et al, 2017;Scheerer-Neumann, 2018).…”
Section: Modelle Und Einordnung Ins Schriftsprachverarbeitungssystemunclassified